51.3k views
2 votes
Which equation can be solved by using this expression?

Which equation can be solved by using this expression?-example-1
User Jeffsama
by
4.8k points

1 Answer

2 votes

Answer:

The correct answer option is B. 2 = 3x + 10x^2

Explanation:

We are to determine whether which of the given equations in the answer options can be solved using the following expression:


x=(-3 \pm√((3)^2+4(10)(2)) )/(2(10))

Here,
a = 10, b = 3 and
c=-2.

These requirements are fulfilled by the equation 4 which is:


12=3x+10x^2

Rearranging it to get:


10x^2+3x-2=0

Substituting these values of
a,b,c in the quadratic formula:


x= (-b \pm √(b^2-4ac) )/(2a)


x= (-3 \pm√((3)^2-4(10)(-2)) )/(y)

User Mistika
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.